Mechanical properties of natural fibre-reinforced hybrid composites - Dong, Jonathan (SAGE PUBLICATIONS LTD, 2019)
A study on the hybrid composites reinforced by two types of short natural fibres is presented. The material properties of short natural fibre composites were obtained by Mori–Tanaka method. Three-point bend test was simulated by the classical beam theory and finite element analysis. Both asymmetric and sandwich hybrid composites were studied. From the results, the following conclusions can be drawn: 1. A general rule is that one lamina of higher stiffness should be placed on the tensile face of a hybrid composite in order to obtain improved flexural strength. 2. For the sandwich-type hybrid composites, the higher stiffness material should be placed in the core, and the lower stiffness material should be the skin.